Overweight and obesity among children at risk of intellectual disability in 20 low and middle income countries. Issue 11 (22nd July 2016) - Savage, A.; Emerson, E.
Abstract: Background: Children with intellectual disability (ID) in high income countries are at significantly greater risk of obesity than their non‐disabled peers. We aimed to estimate the prevalence of overweight and obesity in 3 to 4‐year‐old children who are/are not at risk of ID in low and middle income countries. Method: Secondary analysis of Round 4 and 5 UNICEF Multiple Indicator Cluster Surveys (MICS) from 20 low and middle income countries that included a total of 83 597 3 to 4‐year‐old children. Results: Few differences in risk of overweight or obesity were apparent between 3 and 4‐year‐old children identified as being at risk/not at risk of ID in 20 low and middle income countries. In the two countries where statistically significant differences were observed, prevalence of overweight/obesity was lower among children at risk of ID. Conclusions: These results stand in stark contrast to evidence from high income countries which suggest that children with ID are at significantly increased risk of obesity when compared to their non‐intellectually disabled peers.